Essays on microenterprise growth and financial inclusion - Mukherjee, SW (2023)
This thesis consists of three essays on microenterprise growth and financial inclusion. I focus on two key channels to achieve financial inclusion: (i) encouraging digital technology adoption and (ii) easing frictions in financial markets. Chapter 1 investigates the extent to which learning barriers limit the adoption of productive digital technologies by firms. I leverage a novel digital technology that overcomes financial management issues that arise due to informality and randomly vary the extent to which learning costs are subsidized. Amongst a sample of microenterprises in India I find that temporarily subsidizing learning costs leads to significant increases in adoption. Firms significantly improve business management (through better financial and marketing practices), and in the process learn about the true profitability of their firm, which dampens adoption. Using a dynamic structural model I highlight the need for a multi-dimensional approach to sustain adoption. Chapters 2 and 3 focus on easing financial frictions to increase firm productivity. In Chapter 2 my co-authors and I study whether other financial market frictions — in particular, lack of access to a safe place to save — might limit the benefits of credit. Working with Kenyan farmers, we cross-randomize access to a simple savings product with a harvest-time loan. We find increased farm investment and household consumption amongst those who were offered a savings product in addition to a loan offer. In Chapter 3 my co-authors and I study whether a big push microequity contract can generate firm-level and household-level gains while also recovering the initial investment amount for future investments. Working with women-led microenterprises in India we randomize access to performance contingent microequity contracts and document high demand for this novel financial product and sustained improvements in business performance.